2012
DOI: 10.1128/jb.02186-12
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Binding Properties of the Kingella kingae PilC1 and PilC2 Proteins Have Differential Effects on Type IV Pilus-Mediated Adherence and Twitching Motility

Abstract: Kingella kingae is an emerging bacterial pathogen that is being recognized increasingly as an important etiology of septic arthritis, osteomyelitis, and bacteremia, especially in young children. The pathogenesis of K. kingae disease begins with bacterial adherence to respiratory epithelium, which is dependent on type IV pili and is influenced by two PilC-like proteins called PilC1 and PilC2. Production of either PilC1 or PilC2 is necessary for K. kingae piliation and bacterial adherence. In this study, we set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(75 citation statements)
references
References 54 publications
2
73
0
Order By: Relevance
“…While previous studies found that elimination of the ability of PilY1 (the P. aeruginosa PilC homolog) to bind calcium abolished both adhesion and twitching by preventing surface piliation in P. aeruginosa (25,36), the attenuated adhesion observed in K. kingae (37) and this study for N. gonorrhoeae was not dependent on preventing the surface expression of pili. We found that while the gonococcal calcium-binding-deficient PilC1 mutant was reduced in its ability to adhere to epithelial cells, this defect could not be attributed to a lack of piliation.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…While previous studies found that elimination of the ability of PilY1 (the P. aeruginosa PilC homolog) to bind calcium abolished both adhesion and twitching by preventing surface piliation in P. aeruginosa (25,36), the attenuated adhesion observed in K. kingae (37) and this study for N. gonorrhoeae was not dependent on preventing the surface expression of pili. We found that while the gonococcal calcium-binding-deficient PilC1 mutant was reduced in its ability to adhere to epithelial cells, this defect could not be attributed to a lack of piliation.…”
Section: Discussionmentioning
confidence: 64%
“…PilC from N. gonorrhoeae also has this conserved domain, which has been found in other PilC family members as well ( Fig. 1; see Table S1 in the supplemental material) (37). The focus of this study was to observe whether the calcium-binding domain in the N. gonorrhoeae T4P adhesion protein, PilC, also affected piliation in the same manner as that previously seen in P. aeruginosa.…”
Section: Discussionmentioning
confidence: 86%
“…This observation suggests that piliation offers a selective advantage in the colonization process and at the early stages of the infection, but is detrimental to the bacterium for the invasion of deep body tissues. Additional work by the same research group identified two other genes named pilC1 and pilC2 in physically separated chromosomal locations that encode homologs of the Neisseria PilC proteins that are essential for adherence and piliation [16,19]. Kingella kingae PilC1 and PilC2 proteins have a low level of homology to each other, contain calcium-binding sites and are dispensable for pilus asssembly [16,19].…”
Section: Mechanisms Of Colonization Pilimentioning
confidence: 99%
“…Additional work by the same research group identified two other genes named pilC1 and pilC2 in physically separated chromosomal locations that encode homologs of the Neisseria PilC proteins that are essential for adherence and piliation [16,19]. Kingella kingae PilC1 and PilC2 proteins have a low level of homology to each other, contain calcium-binding sites and are dispensable for pilus asssembly [16,19]. While the PilC1 site is necessary for twitching motility and adherence, the PilC2 site has only a minor influence on motility and no influence on adherence [19].…”
Section: Mechanisms Of Colonization Pilimentioning
confidence: 99%
See 1 more Smart Citation